2023
DOI: 10.1007/s00127-022-02400-0
|View full text |Cite
|
Sign up to set email alerts
|

The engaged community action for preventing suicide (ECAPS) model in Latin America: development of the ¡PEDIR! program

Abstract: Purpose It is estimated that someone dies by suicide every 40 s globally and that 3000 people end their lives daily. Of these deaths, 79% occur in low-resource settings. The very nature of the low-resource settings often serves as a barrier to the adoption and implementation of evidence-based suicide prevention models that have demonstrated success in high-resource countries. As such rates of suicide continue to increase, the workforce of trained mental health providers equipped to effectively eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…This model proves to be both feasible and effective in guiding the development of culturally relevant, community-level intervention. ECAPS adopts a community-based participatory approach, fostering cross-cultural partnerships, resource sharing, and shared decision-making power [ 49 ]. The seven key steps involve: (1) identifying the relevant determinants specific to the community associated with suicide risk; (2) assessing the resources available (and not available) in the community; (3) prioritizing determinants according to available resources; (4) developing a change strategy; (5) implementing the strategy; (6) evaluating outcomes; and (7) identifying next steps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model proves to be both feasible and effective in guiding the development of culturally relevant, community-level intervention. ECAPS adopts a community-based participatory approach, fostering cross-cultural partnerships, resource sharing, and shared decision-making power [ 49 ]. The seven key steps involve: (1) identifying the relevant determinants specific to the community associated with suicide risk; (2) assessing the resources available (and not available) in the community; (3) prioritizing determinants according to available resources; (4) developing a change strategy; (5) implementing the strategy; (6) evaluating outcomes; and (7) identifying next steps.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the ¡PEDIR! Program revealed that the ECAPS model is a feasible and effective framework for use in low-resource settings to guide the development of a culturally relevant community-level intervention to address the systemic, societal, and individual level factors that serve as barriers to suicide prevention [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This model proves to be both feasible and effective in guiding the development of culturally relevant, community-level intervention. ECAPS adopts a community-based participatory approach, fostering cross-cultural partnerships, resource sharing, and shared decisionmaking power [49]. The seven key steps involve: (1) identifying the relevant determinants specific to the community associated with suicide risk; (2) assessing the resources available (and not available) in the community; (3) prioritizing determinants according to available resources; (4) developing a change strategy; (5) implementing the strategy; (6) evaluating outcomes; and (7) identifying next steps.…”
Section: Discussionmentioning
confidence: 99%
“…Conviene destacar que, en el caso peruano, los alumnos llegan a la universidad con dichos problemas (12,13,15) . A nivel mundial se vienen implementando programas de prevención (16) que suelen incluir líneas de ayuda, campañas de concientización y capacitación de profesionales de la salud y educación (17) . En la UNMSM, nos apoyamos en la Teoría Informacional de la Personalidad de Pedro Ortiz, la cual propone que el hombre nace modelado genéticamente como miembro de la especie Homo Sapiens para, luego de ser educado y humanizado por la sociedad, culminar tal proceso al final de la adolescencia y convertirse en una personalidad (18,19,20) .…”
Section: Alberto Peralesunclassified